Estimating Measurement Invariance on Emotional Intelligence Scale across Gender and Age among Undergraduates - Oladunmoye , E. O.; Agbor, Enwa Comfort; Olabisi, Oladimeji Lateefah; Oyadeyi, Joseph Babajide (Universitas Pendidikan Ganesha, 2024)
Critical concerns in estimating measurement invariance of the Schutte emotional intelligence scale by gender and age among undergraduate students. This research aims to analyze five research questions, which are analyzed using exploratory factor analysis together with a correlation matrix to explain the relationship between the variables studied. This study used a cross-sectional, multi-method, multi-trait research design, drawing on a random sample of 300 first-year undergraduate students selected from three universities. The Schutte Emotional Intelligence Scale, with a Cronbach's alpha coefficient of 0.872, served as the main instrument for data collection. The results showed that the Schutte Emotional Intelligence Scale demonstrated good model fit, as evidenced by the chi-square goodness-of-fit statistic (X^2(220) = 955.19, p < 0.05). This shows that the Schutte Emotional Intelligence Scale shows strong suitability with the model used in this research. However, it is important to consider that the chi-square goodness-of-fit may be affected by sample size, prompting examination of additional model fit indices. Further, within the Nigerian population, 23 out of the 33 items in the Schutte Emotional Intelligence Scale were found to be suitable for individuals in the age range of adolescence and emerging adulthood.